Stability of tree in structural cell in unsaturated soil mixtures - Muyassarah Mohamed (2016)
Singapore is a green urban city with millions of trees planted around the country. Many of them are located beside pavements and roads. Concrete pavements and roads laid above compacted soil leads it to carry the traffic load near the trees reducing the space for roots to spread and as a consequence also limit the root growth. Hence, structural cells have been proposed to improve this problem since structural cells provide spaces for root to grow.